Fast-ion pressure dominating the mass dependence of the core heat transport in ASDEX Upgrade H-modes. (17th February 2021) - Schneider, P.A.; Bonanomi, N.; Angioni, C.; Weiland, M.; Cavedon, M.; David, P.; Fischer, R.; Hennequin, P.; Hobirk, J.; Kappatou, A.; Kurzan, B.; McDermott, R.M.; et al.
Abstract: H-mode plasmas in ASDEX Upgrade (AUG) using different hydrogen isotopes are analysed with respect to their core transport properties. The experimental results are discussed and we present gyrokinetic simulations which are able to reproduce the experimental observations. A novel strategy allows us to disentangle core and pedestal physics by mitigating the isotopic dependence of pedestal properties while keeping the heat and particle sources the same. Matched pedestal profiles are obtained between hydrogen (H) and deuterium (D) plasmas when increasing the triangularity in H plasmas with respect to D plasmas. In the core of these plasmas little isotopic dependence is observed when the fast-ion content is low W fast / W th < 1/3. Quasi-linear modelling with TGLF reproduces the experimental trends under these conditions. For larger fast-ion fractions an isotope dependence is observed in the core heat transport. This is related to a difference in fast-ion stabilization of turbulent transport. The fast-ion pressure in H and D plasmas is different due to the mass dependence in the fast-ion slowing down time as well as to operational restrictions when heating with H neutral beam injection (H-NBI) or D-NBI. Typically, W fast, H < 1/2 W fast, D for comparable NBI heating powers in AUG. The gyrokinetic analysis shows that linear growth rates of ITG modes do not show a pure gyro-Bohm mass dependence, but follow the experimentally observed mass dependence when taking collisions, EM-effects and fast ions into account. Non-linear gyrokinetic simulations reproduce the experimental heat fluxes for different isotopes when fast ions are included. This highlights the role of the fast-ion pressure as a key element to explain the observed differences in the core of H and D plasmas.